Saudi's Growth and Financial Spillovers to Other GCC Countries : An Empirical Analysis - Adedeji, Olumuyiwa (IMF Working Papers; Working Paper ;, 2018)
This paper examines real and financial linkages between Saudi Arabia and other GCC countries. Growth spillovers from Saudi Arabia to Bahrain are found to be sizeable and statistically significant, but those to other GCC countries are not found to be significant. Equity market movements in Saudi Arabia are found to have significant implications for other GCC countries, while there is no evidence of co-movements in bonds markets. These findings suggest some degree of interdependence among GCC countries.